2020
DOI: 10.1038/s41598-020-75514-7
|View full text |Cite|
|
Sign up to set email alerts
|

A combination of electrochemistry and mass spectrometry to monitor the interaction of reactive species with supported lipid bilayers

Abstract: Reactive oxygen and nitrogen species (RONS), e.g. generated by cold physical plasma (CPP) or photodynamic therapy, interfere with redox signaling pathways of mammalian cells, inducing downstream consequences spanning from migratory impairment to apoptotic cell death. However, the more austere impact of RONS on cancer cells remains yet to be clarified. In the present study, a combination of electrochemistry and high-resolution mass spectrometry was developed to investigate the resilience of solid-supported lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 103 publications
(107 reference statements)
1
14
0
Order By: Relevance
“…The dependence of the protective effect on SM fraction in PLPC bilayers is in agreement with electrochemical results (30% and 42% for lipid bilayers with 25 and 75% SM, respectively). Electron paramagnetic resonance (EPR) studies on similar set up in our previous work indicated that the hydroxyl radical, superoxide anion and hydrogen peroxide are the main reactive species produced in aqueous phase during plasma treatment [ 66 ]. Interestingly, these reactive species play a significant role in cataract formation in eye [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The dependence of the protective effect on SM fraction in PLPC bilayers is in agreement with electrochemical results (30% and 42% for lipid bilayers with 25 and 75% SM, respectively). Electron paramagnetic resonance (EPR) studies on similar set up in our previous work indicated that the hydroxyl radical, superoxide anion and hydrogen peroxide are the main reactive species produced in aqueous phase during plasma treatment [ 66 ]. Interestingly, these reactive species play a significant role in cataract formation in eye [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, these reactive species play a significant role in cataract formation in eye [ 17 ]. Several reports indicated that hydrogen peroxide does not generate a direct oxidative damage in lipid bilayer [ 66 , 83 ]. Therefore, short-lived reactive species play the dominant role in PLPC oxidation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The combination of electrochemistry (EC) and mass spectrometry (MS) has become a powerful and versatile strategy that allows one to characterize a broad range of electrochemical and biological reactions, and extends the scope of analytes for mass spectrometric analysis. [1][2][3][4][5][6][7][8][9][10][11][12] In this hyphenation, MS has often been used due to its high sensitivity and specificity for determination of electrochemical reactions, providing structural information unavailable from EC methods. Electrochemical reactions can be used to oxidize or reduce analytes so as to improve the ionization of analytes for mass spectrometric analysis.…”
Section: Introductionmentioning
confidence: 99%